Econometric study of British tourist expenditure in Ireland - Barry, Kevin; O' Hagan, John (Economic & Social Studies, 1972)
The amount of research devoted to tourism is not commensurate with its economic importance. The reasons for this scarcity of research are numerous and mostly concern the inherent difficulties of the subject. The purpose of this paper is to rectify in part this lack by means of an econometric analysis of the determinants of expenditure by British tourists and recreational tourists in Ireland.
Keywords: British Tourists; Ireland; Economy